Problematika Etika Bermedia Sosial Mahasiswa Calon Guru: Studi Literatur dalam Perspektif Etika Profesi Keguruan - Dwi Siska; Aeni Shiva Sal-sabila; Nur Azka Dhiya'ul Aulia; Muhlisin Muhlisin; Abul Mafaakhir (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to examine the moral dilemmas faced by prospective teachers when using social media from the perspective of professional ethics. Social media is increasingly becoming an open public space that influences students’ behavior and professional identity due to the rapid growth of digital technology. However, these changes are often not accompanied by sufficient ethical awareness. By reviewing relevant materials, such as books, scientific articles, and journals. This study employs a qualitative approach using a literature review method. The results indicate that inappropriate communication, impulsive reactions, excessive information sharing, and the blurring of boundaries between the personal and professional spheres are examples of ethical issues. These issues highlight a mismatch between students’ actual behavior in digital contexts and their conceptual knowledge of ethics. Additionally, limited digital literacy, social pressure in online environments, and the inadequate internalization of teachers’ professional ethical norms are the primary contributing factors. From a professional ethics perspective, prospective educators must uphold values such as accountability, integrity, and exemplary conduct in both physical and virtual environments. To address this issue, it is crucial to enhance self-awareness, integrate ethics education into teacher preparation programs, and develop digital ethics literacy.